Advanced loading variations in the push-up exercise - Ghigiarelli, J. J. (Strength and Conditioning Journal, 2013)
The exercise technique for the push-up using 2 different loading styles is described and demonstrated in this column. Several progressions and variations for this exercise are also discussed.